Pengembangan Media Pembelajaran MEG (Monopoly Education Game) Mata Pelajaran IPAS Kelas IV SDN 1 Gunungsari - Dinda Anggi Pravista; Mega Isvandiana Purnamasari; Erna Setyawati (Scholarly Journal of Elementary School, 2026)
This study aims to describe the development process, assess eligibility, and examine students' responses to the MEG (Monopoly Education Game) learning media. This research uses the Research and Development (R&D) method with the ADDIE development model, which includes the Analysis, Design, Development, Implementation, and Evaluation stages. The subject of the study is a grade IV student of SD Negeri 1 Gunungsari. Data collection techniques include observation, interviews, questionnaires, and documentation. The research data were obtained from validation results by media and material experts and from student response questionnaires. The validation results from media experts showed 89.4% in the very valid category, while the validation results from material experts showed 95.3% in the very valid category. Meanwhile, the student response questionnaire yielded a 92.3% response rate, with very interesting results. Based on these results, the MEG (Monopoly Education Game) learning media was declared suitable for use as a learning medium for the science subject of Indonesian Cultural Wealth in grade IV of elementary school.